Screening of risk for non-specific low-back pain: do occupational hazards matter? - Serranheira, Florentino; Campbell, Paul; Sousa-Uva, António (La Medicina del Lavoro, 2017)
Low back pain (LBP) is very common; lifetime prevalence is high with estimates of 50% to 70%, and up to half the people with LBP will seek some form of healthcare. Global burden of disease findings show that back pain is the leading cause of disability adjusted life years (DALYs) in Western Europe and Australia, and is ranked 6th of the top 25 diseases associated with disability (6). As a consequence LBP has a significant impact on the individual, and on the wider economy due to substantial healthcare costs and loss of productivity due to sickness absence. [...]